The Use of Blockchain in Financial Area: A Systematic Mapping Study - Luz, Maicon Azevedo da; Oliveira, Kleinner Silva Farias de (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
Blockchain is a technology for decentralized transactions that has been widely used with cryptocurrencies such as Bitcoin. Many studies have been conducted in the last decades, approaching cryptocurrencies, and blockchain technology, more strongly in the context of financial transactions. However, little has been done to provide a panoramic view of the current literature; as a consequence, a careful understanding of the state-of-the-art papers remains limited and inconclusive. This study, therefore, aims to classify and provide a thematic analysis of studies on the use of blockchain in the context of financial area, thus allowing to create a clear systematic map of the current literature, and identify challenges and research opportunities. To achieve these objectives a systematic mapping study (SMS) approach was performed to answer 6 research questions. In total, 1884 studies were reviewed from 6 data sources, being 23 studies selected after a careful filtering process. The main findings were: (1) Over 65% of the selected studies concentrated on adopting two blockchain platforms named Hyperledger Fabric and Ethereum; (2) Over 60% used blockchain technology to increase security; (3) Most studies did not reveal the consensus algorithm used; (4) Fintech (or Bank) and loan were the most explored application areas; (5) Over 60% focused on producing prototype rather than frameworks; and (6) most studies were published in conferences. This study can benefit research community by generating a map of the literature, serving as a starting point for future researches. Moreover, this study reports some challenges worth investigating.